Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan (Studi Kasus Waroeng Aneka Sambel Jombang) - Muhammad Yusuf (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
This research purpose to look for occur or does not occur influence between product quality and price toward customers satisfaction in Waroeng Aneka Sambel Jombang. The kind of research used is technic quantitative descriptive association. Take of sample by slovin margin error 5 percents amount 139 customers. This research using technic with collection the questioner data, interview, documentation, and observation. This analysis data using statistic methods of using validity and reliable, classic assumption test, hypothetical test, by multiple linier regressions formula. The results of this research showed that 1) The product quality has a positive effects to customers each partial 2) The price have a significant effects to customers 3) The quality of the product and the price simultaneously have a influenced towards toward customers satisfaction in Waroeng Aneka Sambel Jombang.